2023
DOI: 10.1093/mnras/stad1841
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy cluster rotation revealed in the MACSIS simulations with the kinetic Sunyaev–Zeldovich effect

Abstract: The kinetic Sunyaev-Zeldovich (kSZ) effect has now become a clear target for ongoing and future studies of the cosmic microwave background (CMB) and cosmology. Aside from the bulk cluster motion, internal motions also lead to a kSZ signal. In this work, we study the rotational kSZ effect caused by coherent large-scale motions of the cluster medium using cluster hydrodynamic cosmological simulations. To utilise the rotational kSZ as a cosmological probe, simulations offer some of the most comprehensive data set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…In a series of recent works, SZ and X-ray studies have been suggested to constrain models of baryonic physics, and specifically the role of AGN feedback in determining the thermodynamic properties of the ICM (e.g., Acharya et al 2021;Eckert et al 2021;Chadayammuri et al 2022;Kar Chowdhury et al 2022;Kim et al 2022;Yang et al 2022;Altamura et al 2023). In a previous study, Brownson et al (2019) proposed using the FABLE cosmological simulations and that ALMA has the potential to constrain AGN feedback models through SZ observations.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…In a series of recent works, SZ and X-ray studies have been suggested to constrain models of baryonic physics, and specifically the role of AGN feedback in determining the thermodynamic properties of the ICM (e.g., Acharya et al 2021;Eckert et al 2021;Chadayammuri et al 2022;Kar Chowdhury et al 2022;Kim et al 2022;Yang et al 2022;Altamura et al 2023). In a previous study, Brownson et al (2019) proposed using the FABLE cosmological simulations and that ALMA has the potential to constrain AGN feedback models through SZ observations.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…When working with real data, this technique will also help in removing the bias due to the CIB, as well as any other foregrounds correlated with the clusters under study. We did not include the effects of the rotational kSZ [78][79][80][81] or the moving-lens effect [82,83], which are also expected to produce a dipole signal. However, the orientation of the dipole will be aligned along the direction of the cluster rotation in the former and the direction of the large-scale velocity field in the latter, which are both not correlated with the direction of the background CMB gradient.…”
Section: Discussionmentioning
confidence: 99%